2020
DOI: 10.4236/ojas.2020.101008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Velocity and Vertically-Suspended Structures on Rainbow Trout Rearing Performance

Abstract: This study evaluated the effects of two water velocities and three types of vertically-suspended environmental enrichment during the rearing of juvenile rainbow trout (Oncorhynchus mykiss; mean ± SE, initial weight 4 ± 1 g and total length 71 ± 2 mm) in 1.8-m diameter circular tanks. The 2 × 3 experimental design used two velocities (12.2 cm•s −1 and 30.5 cm•s −1) and three structural treatments (aluminum rod array, plastic spheres, or no structure). After 116 days, the fish reared without any structure (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
4
9
1
Order By: Relevance
“…Despite the relatively high loading densities, the feed conversion ratios observed in this experiment are similar to those previously reported for rainbow trout [25] [45]. At 2.3 to 2.6, the specific growth rates, which is basically the percentage growth per day of fish, in this study were also similar to those reported by Huysman et al [32] and Voorhees et al [45]. Condition factors were also similar to those reported previously for rainbow trout [25]…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Despite the relatively high loading densities, the feed conversion ratios observed in this experiment are similar to those previously reported for rainbow trout [25] [45]. At 2.3 to 2.6, the specific growth rates, which is basically the percentage growth per day of fish, in this study were also similar to those reported by Huysman et al [32] and Voorhees et al [45]. Condition factors were also similar to those reported previously for rainbow trout [25]…”
Section: Discussionsupporting
confidence: 91%
“…However, at higher velocity levels that produced vigorous exercise, positive effects on fish rearing performance were not observed. This is similar to the results of other studies using high velocities for exercise or not allowing for any rest periods [25] [44] [45], which all likely produced exercise fatigue [42] [34]. It must be noted however, that the results from using structure in this study differ from those of White et al [28], Huysman et al [31], and Jones et al [33].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations